Establishing a link between risk tolerance, investor personality and behavioural finance in South Africa - Zandri Dickason; Sune Ferreira (Cogent Economics & Finance, 2018)
The main objective of this paper was to establish which behavioural finance biases are associated with a certain level of risk tolerance and investor personality. Furthermore, the study aimed to indicate how these behavioural finance biases can influence investment decisions. Since behavioural finance is becoming more essential in the investment industry, further research within a South African context was regarded as necessary. Results indicated that investors with a low-risk tolerance level and a conservative investor personality are subject towards loss aversion and mental accounting biases. Investors with a high-risk tolerance level are mostly subject towards the self-control bias. The significance of this study will enable investment companies to more accurately profile their investors and to offer more refined investment options.
Keywords: D81; G11; G2; 330; behavioural finance; investors; investor personalities; risk tolerance; investment decisions